Oxidative stress and APO E polymorphisms in Alzheimer's disease and in mild cognitive impairment. (August 2013) - Chico, L.; Simoncini, C.; Lo Gerfo, A.; Rocchi, A.; Petrozzi, L.; Carlesi, C.; Volpi, L.; Tognoni, G.; Siciliano, G.; Bonuccelli, U.
Abstract A number of evidences indicates oxidative stress as a relevant pathogenic factor in Alzheimer's disease (AD) and mild cognitive impairment (MCI). Considering its recognized major genetic risk factors in AD, apolipoprotein (APO E) has been investigated in several experimental settings regarding its role in the process of reactive oxygen species (ROS) generation. The aim of this work has been to evaluate possible relationships between APO E genotype and plasma levels of selected oxidative stress markers in both AD and MCI patients. APO E genotypes were determined using restriction enzyme analysis. Plasma levels of oxidative markers, advanced oxidation protein products, iron-reducing ability of plasma and, in MCI, activity of superoxide dismutases were evaluated using spectrophotometric analysis. We found, compared to controls, increased levels of oxidized proteins and decreased values of plasma-reducing capacity in both AD patients (p < 0.0001) and MCI patients (p < 0.001); the difference between AD and MCI patients was significant only for plasma-reducing capacity (p < 0.0001), the former showing the lowest values. Superoxide dismutase activity was reduced, although not at statistical level, in MCI compared with that in controls. E4 allele was statistically associated (p < 0.05) with AD patients. When comparing different APO E genotype subgroups, no difference was present, as far as advanced oxidation protein products and iron-reducing ability of plasma levels were concerned, between E4 and non-E4 carriers, in both AD and MCI; on the contrary, E4 carriers MCI patients showed significantly decreased (p < 0.05) superoxide dismutase activity with respect to non-E4 carriers. This study, in confirming the occurrence of oxidative stress in AD and MCI patients, shows how it can be related, at least for superoxide dismutase activity in MCI, to APO E4 allele risk factor.